Employee Engagement and its Impact on Organization’s Performance: Case Study (Global Journal of Management and Business Research, 2023)
Engaging employees effectively is vital for organizations that want to outperform their competitors Extensive research and studies have been conducted on this topic emphasizing the importance of employees physical and mental well-being for their engagement and contributions to company advancement Therefore fostering employee engagement becomes a powerful tool for organizations to solidify their market position This study will address the concept of employee engagement and its drivers through a literature review Additionally a case study will be presented focusing on one of Saudi Aramco s leading organizations that achieved commendable scores in a corporate employee engagement survey The findings of this review establish a direct correlation between engaged employees and desired performance and outcomes for companies
Keywords: employee; employee engagement; performance; communication